2013
DOI: 10.1590/s1519-69842013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fish assemblages similarity above and below a dam in a Neotropical reservoir with partial blockage

Abstract: Damming rivers disrupts the water flow and changes the ichthyofauna organisation. We investigated an impoundment with permanent connection and homogeneous environmental conditions between the zones above and below the dam. Temperature was comparatively higher during wet season irrespective of zone, and both zones had higher dissolved oxygen, conductivity and transparency in the dry season. A total of 1687 individuals comprising 27 species were collected in the downriver zone, while the reservoir had 879 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…This scenario reinforces the importance of the physical features of reservoirs to determine the functional space to be filled by different fish species. Likewise, these results show that the loss of hydrological connectivity disrupts population flows within the riverine system, which together with the introduction of non‐native species culminate in highly distinct taxonomic structures even in reservoirs close to each other (Araújo et al, 2013; Pelicice et al, 2015). The similar trends observed per season (dry or wet) revealed that similar assembly processes operate in all reservoirs over short‐term temporal dimensions, reinforcing the strength of spatial patterns.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This scenario reinforces the importance of the physical features of reservoirs to determine the functional space to be filled by different fish species. Likewise, these results show that the loss of hydrological connectivity disrupts population flows within the riverine system, which together with the introduction of non‐native species culminate in highly distinct taxonomic structures even in reservoirs close to each other (Araújo et al, 2013; Pelicice et al, 2015). The similar trends observed per season (dry or wet) revealed that similar assembly processes operate in all reservoirs over short‐term temporal dimensions, reinforcing the strength of spatial patterns.…”
Section: Discussionmentioning
confidence: 92%
“…River damming creates new ecosystems, changing physical and chemical characteristics by transforming lotic systems into lentic habitats (Agostinho et al, 2016; Granzotti et al, 2018; Tundisi & Matsumura‐Tundisi, 2003). These changes promote habitat loss, changes in resource availability, and limitation of riverine connectivity, increasing extinction risk of endemic taxa and favoring invasions by non‐native species and prevalence of generalist species (Araújo et al, 2013; Fitzgerald et al, 2018; Liermann et al, 2012). Dams thus can act as environmental filters strongly selecting functional traits, and generating long‐lasting changes to the structure of fish assemblages (Lima et al, 2018; Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, river damming is one of the most influential anthropogenic modifications to riverine ecosystems (Santos & Araújo, 2015). It affects many key aspects of the ecosystem such as hydrologic connectivity, which is crucially important to fish and other aquatic organisms (Araújo et al, 2013). Impounded streams rapidly change their characteristics from being relatively shallow flowing habitats to being deeper stagnant watercourses, which native stream fishes have likely not experienced during their evolution (Baxter, 1977).…”
Section: Introductionmentioning
confidence: 99%